Effect of arc-shaped twisted-baffles on augmented heat transfer in a rectangular duct - Pongjet Promvonge; Arnut Phila; V. Chuwattanakul; S. Chokphoemphun; Smith Eiamsa–ard; Naoki Maruyama; Masafumi Hirota (Case Studies in Thermal Engineering, 2023)
In this current work, the effect of utilizing arc-shaped twisted-baffles (T-ABs) in a rectangular air channel on thermal performance factor (TPF) has been experimentally studied. In these experiments, the influence of the changes in parameters such as dimensions of pitch ratio (p/w), attached arc-shape angle (α), and Reynolds number (Re) are explored. The comparisons demonstrate that a channel mounted with arc-shaped twisted-baffles yielded considerably greater Nusselt numbers than a smooth channel, possibly attributable to multiple-impinging jets near the channel surface. Heat transfer enhancements of twisted arc-shaped baffles (T-AB) having larger attack angles were superior to those having smaller attack angles. The one with α = 90o offered greater heat transfer rates than the ones with α = 20o, 40o, 60o, and 80o by approximately 8%, 7%, 4%, and 2%, respectively. The superior heat transfer was attributed to the better contact between the working fluid and heat transfer surfaces. In addition, utilizing arc-shaped twisted-baffles with the lowest p/w of 4.0, in a channel produced stronger vortices and multiple impinging jets, which caused better fluid mixing than other p/w. The optimum condition is achieved using T-ABs at an attached arc-shape angle of α = 90o, p/w = 4.0 and Re = 4000, where the heat transfer rate (Nu), friction factor (f) and TPF are found to be, respectively, 3.31, 4.68 and 1.98 times greater than those of a plain channel.
Keywords: Heat Transfer Mechanisms; Fluid Dynamics and Turbulent Flows; Heat Transfer and Optimization